A Systematic Review of the Effect of Oral Rinsing with H2O2 on Clinical and Microbiological Parameters Related to Plaque, Gingivitis, and Microbes - Francisco Wilker Mustafa Gomes Muniz; Juliano Cavagni; Gerson Pedro José Langa; Bernal Stewart; Zilson Malheiros; Cassiano Kuchenbecker Rösing (International Journal of Dentistry)
Background. Hydrogen peroxide (H2O2) has been used for more than a century clinically to control plaque and gingival inflammation, with unclear supporting evidence. Aim. The aim of the present systematic review of the literature is to assess the effect of mouth rinses with H2O2 on dental plaque, gingival inflammation, and oral microorganisms. Methods. Five databases (PubMed, Scopus, Embase, Cochrane Library, and Web of Science) were searched with the following focused question: what is the effect of hydrogen peroxide, in comparison to chlorhexidine or to a placebo solution, in oral microbiota control, dental plaque, and gingival inflammatory outcomes? Two independent examiners retrieved the articles and evaluated the evidence. Results. The majority of included studies were performed with 1.5% H2O2. Results related to plaque accumulation generally demonstrate a slightly better effect of H2O2 as compared to placebo mouth rinses, however with a lower performance as compared to chlorhexidine. In terms of gingival inflammation, H2O2 performs better than placebo and more clearly demonstrates an anti-inflammation effect. No studies evaluated the effect of H2O2 against viruses or fungi. In terms of bacteria, H2O2 demonstrates an antibacterial effect. Conclusion. Rinsing with H2O2 has the potential to affect plaque, gingivitis, and oral bacteria, as compared to placebo. However, the antibacterial results are not comparable to the performance of chlorhexidine.